1999
DOI: 10.1210/jcem.84.10.6029
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Meiosis in Intratesticular Germ Cells from Subjects Affected by Classic Klinefelter’s Syndrome

Abstract: Azoospermic subjects affected by Klinefelter's syndrome may occasionally show the presence of intratesticular residual foci of spermatogenesis, and the retrieval of mature spermatozoa from the testis may permit fertility and paternity by means of intracytoplasmic sperm injection. Previous studies have demonstrated that these subjects show the presence of an increased incidence of hyperaploid spermatozoa. Here we analyzed, by fluorescence in situ hybridization using specific probes for chromosomes 8, X, and Y, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 17 publications
1
31
0
3
Order By: Relevance
“…Although there has been much concern about the high aneuploidy rates of spermatozoa in men with KS (Foresta et al ., ; Aksglaede et al ., ; Bakircioglu et al ., ), over 100 births from IVF/ICSI have been documented in the literature with no aneuploid children reported (Bourne et al ., ; Hinney et al ., ; Komori et al ., ; Okada et al ., ; Vicdan et al ., ) A study by Yarali et al . demonstrated that pregnancy and implantation rates were comparable for a group of 33 patients with KS (39 and 23%) vs. a group of 113 men with non‐obstructive azoospermia and a normal karyotype undergoing testicular sperm extraction (TESE)/ICSI (33 and 26%).…”
Section: Genetic Tests For Non‐obstructive Azoospermia/severe Oligospmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there has been much concern about the high aneuploidy rates of spermatozoa in men with KS (Foresta et al ., ; Aksglaede et al ., ; Bakircioglu et al ., ), over 100 births from IVF/ICSI have been documented in the literature with no aneuploid children reported (Bourne et al ., ; Hinney et al ., ; Komori et al ., ; Okada et al ., ; Vicdan et al ., ) A study by Yarali et al . demonstrated that pregnancy and implantation rates were comparable for a group of 33 patients with KS (39 and 23%) vs. a group of 113 men with non‐obstructive azoospermia and a normal karyotype undergoing testicular sperm extraction (TESE)/ICSI (33 and 26%).…”
Section: Genetic Tests For Non‐obstructive Azoospermia/severe Oligospmentioning
confidence: 99%
“…Fertilization rates were also similar in these two groups, however, preimplantation genetic diagnosis revealed that only 59% of the embryos from KS patients had a normal karyotype (Yarali et al ., ) It has been demonstrated that frequency of XY spermatozoa, the main cause of aneuploidy in men with KS, does increase significantly with paternal age (Arnedo, ). Furthermore, many have put forward evidence suggesting that spermatogenesis potential decreases with advancing age in men with KS (Foresta et al ., ; Aksglaede et al ., ; Bakircioglu et al ., ). This has prompted many to argue for the need of surgical sperm extraction through microsurgical testicular sperm extraction (microTESE) and sperm banking at a young age.…”
Section: Genetic Tests For Non‐obstructive Azoospermia/severe Oligospmentioning
confidence: 99%
“…Although the phenotypic spectrum of the syndrome is wide, testicular dysfunction is a constant clinical finding, characterized by small testes, elevated gonadotropins from midpuberty onwards and, with rare exceptions, absence of spermatozoa in the ejaculate . Therefore, most frequently, the diagnosis takes place during the workup of patients seeking fertility . Most cases show a 47XXY karyotype, but some patients have mosaicisms (ie 46XY/47XXY) or chromosome aneuploidies with more than one extra X chromosome such as 48XXXY and 49XXXXY …”
Section: Introductionmentioning
confidence: 99%
“…Only 0.4% of male infertility cases have been attributed to congenital unilateral absence of the vas deferens (CUAVD) (Weiske, Salzler, Schroeder‐Printzen, & Weidner, ). KS is seen in 3% of infertile males (Foresta et al., ). Cases with the combination of these abnormalities are extremely rare, and the incidence is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Klinefelter's syndrome, 47, XXY (KS), is characterised by a progressive testicular failure causing small firm testes, androgen deficiency and azoospermia (Klinefelter, Reifenstein, & Albright, ). This syndrome is the most common known genetic cause of azoospermia among men (Lanfranco, Kamischke, Zitzmann, & Nieschlag, ) and seen in 3% of infertile males (Foresta et al., ). Internal or external genital abnormalities such as congenital uni/bilateral absence of the vas deferens are very rare in KS.…”
Section: Introductionmentioning
confidence: 99%